Early Jurassic diversification of pycnodontiform fishes (Actinopterygii, Neopterygii) after the end-Triassic extinction event: evidence from a new genus and species, Grimmenodon aureum. Issue 4 (4th July 2017) - Stumpf, Sebastian; Ansorge, Jörg; Pfaff, Cathrin; Kriwet, Jürgen
ABSTRACT: A new genus and species of pycnodontiform fishes, Grimmenodon aureum, from marginal marine, marine-brackish lower Toarcian ( Harpoceras exaratum ammonite subzone) clay deposits of Grimmen in northeastern Germany is described. The single specimen represents a diagnostic left prearticular dentition characterized by unique tooth arrangement and ornamentation patterns. Grimmenodon aureum, gen. et sp. nov., is the second unambiguously identified pycnodontiform species from the Early Jurassic, in addition to Eomesodon liassicus from the early Lower Jurassic of western Europe. We also report an indeterminate pycnodontiform tooth crown from the upper Pliensbachian ( Pleuroceras apyrenum ammonite subzone) of the same site. The material expands the Early Jurassic range of pycnodontiforms significantly northwards and confirms their presence before and immediately following the onset of the Toarcian Oceanic Anoxic Event (T-OAE) in the marginal marine ecosystems south of the Fennoscandian Shield. Moreover, the new records indicate that the Early Jurassic diversity of pycnodontiform fishes was greater than previously assumed and probably equaled that of the Late Triassic. Therefore, it is hypothesized that the Triassic-Jurassic mass extinction event did not affect pycnodontiform fishes significantly. Micro-computed tomography was used to study the internal anatomy of the prearticular of Grimmenodon aureum, gen. et sp. nov. Our results show that no replacement teeth were formed within the tooth-bearing bone but rather were added posteriorly to functional teeth.